2012
DOI: 10.1039/c2ra20141k
|View full text |Cite
|
Sign up to set email alerts
|

Predictive methods for the estimation of thermophysical properties of ionic liquids

Abstract: While the design of products and processes involving ionic liquids (ILs) requires knowledge of the thermophysical properties for these compounds, the massive number of possible distinct ILs precludes their detailed experimental characterization. To overcome this limitation, chemists and engineers must rely on predictive models that are able to generate reliable values for these properties, from the knowledge of the structure of the IL. A large body of literature was developed in the last decade for this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 167 publications
1
92
0
3
Order By: Relevance
“…To explore the "tuneability" and "designability" features of ILs, predictive QSPR models have to be developed to relate the properties to the chemical structure or other physicochemical properties. 4,9 Such models should also be rigorously validated in order to prove their predictive capacity and applicability to a new set of ILs. Although ILs were originally promoted as green solvents, studies have also shown that ionic liquids, as any organic solvent, may have some degree of toxicity to the various organisms of the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the "tuneability" and "designability" features of ILs, predictive QSPR models have to be developed to relate the properties to the chemical structure or other physicochemical properties. 4,9 Such models should also be rigorously validated in order to prove their predictive capacity and applicability to a new set of ILs. Although ILs were originally promoted as green solvents, studies have also shown that ionic liquids, as any organic solvent, may have some degree of toxicity to the various organisms of the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop mathematical models to predict the various property endpoints of ILs. Quantitative structure-property/activity relationship (QSPR/QSAR) methods [7][8][9] would help to develop quantitative models capable of predicting the properties directly from molecular structure information.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is mainly based on the experimental trial-error means. More recently, many methods including ab initio calculation, molecular simulation, quantum chemistry, and correlation have been successfully applied to calculate and/or predict the physical properties of ionic liquids [123,124]. Not only physical, but also chemical and biological properties of ionic liquids can be predicted by these methods.…”
Section: Future Perspective On Rational Design Of Ionic Liquids For Bmentioning
confidence: 98%
“…Sin embargo, los resultados son similares a los obtenidos con el MCG de Joback-Reid. Esto porque si bien la estructura tiene relevancia en el valor de una determinada propiedad, esta no es la única característica que determina el valor por ejemplo de la temperatura de fusión; y menos en los casos de líquidos iónicos (Coutinho et al, 2012 Tetradecyl-tripentyl-ammoniumbromide 9.0…”
Section: Ii) Extensión Al Cálculo De Tf De Líquidos Iónicosunclassified